2019
DOI: 10.1016/j.devcel.2018.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Epigenomics Reveals that RNA Polymerase II Pausing and Chromatin Domain Organization Control Nematode piRNA Biogenesis

Abstract: Summary Piwi-interacting RNAs (piRNAs) are important for genome regulation across metazoans, but their biogenesis evolves rapidly. In Caenorhabditis elegans , piRNA loci are clustered within two 3-Mb regions on chromosome IV. Each piRNA locus possesses an upstream motif that recruits RNA polymerase II to produce an ∼28 nt primary transcript. We used comparative epigenomics across nematodes to gain insight into the origin, evolution, and mechanism of nematode piRNA biogenesis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(86 citation statements)
references
References 70 publications
(126 reference statements)
8
66
0
Order By: Relevance
“…Two large clusters of piRNAs are found in C. elegans on chromosome IV (Ruby et al, 2006), while clustering of piRNA loci is not observed in P. pacificus (de Wit et al, 2009) nor in H. contortus (Winter et al, 2012). Recent work by Beltran et al (2019) also identified differences in the chromatin structure of domains encoding piRNAs between nematode species, suggesting different modes of regulation. Two types of genomic organization of piRNA genes were characterized: P-type (e.g.…”
Section: Nematode Pirnasmentioning
confidence: 97%
“…Two large clusters of piRNAs are found in C. elegans on chromosome IV (Ruby et al, 2006), while clustering of piRNA loci is not observed in P. pacificus (de Wit et al, 2009) nor in H. contortus (Winter et al, 2012). Recent work by Beltran et al (2019) also identified differences in the chromatin structure of domains encoding piRNAs between nematode species, suggesting different modes of regulation. Two types of genomic organization of piRNA genes were characterized: P-type (e.g.…”
Section: Nematode Pirnasmentioning
confidence: 97%
“…Transcription of these genes requires a protein named PRDE-1 and the transcription factor SNPC-4 (Kasper et al 2014;Weng et al 2018), the latter of which is also known to be involved in transcription of other short structural RNAs, such as snRNAs and splice leader RNAs (Kasper et al 2014). An evolutionary analysis of 21U RNA loci in diverse nematodes has revealed that 21U loci may have evolved from snRNA loci (Beltran et al 2019). These loci include both the strongly conserved U1 and U2 loci as well as loci producing so-called splice leader RNAs (SL1 and SL2) that are trans-spliced to the 5 ′ ends of a large fraction of all mRNAs in C. elegans (Blumenthal 2012).…”
mentioning
confidence: 99%
“…Perhaps RPB-9 is part of an ancient network which, together with SNPC-4 (Kasper et al, 2014) and the USTC complex , has been recruited to direct transcription at piRNA loci. The recent discovery that motif-dependent piRNA units share evolutionary similarities with the highly conserved snRNA genes (Beltran et al, 2019) , together with the fact that transcription of both these types of loci depends on the Integrator complex (Baillat et al, 2005;Ezzeddine et al, 2011Ezzeddine et al, , 2012Uguen and Murphy, 2003) (Beltran et al, 2020 co-submitted), seem to favor this hypothesis. Whether rpb-9 is required for transcription of snRNA genes in C. elegans is however currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…At non polyadenylated-type loci, such as those encoding for small nuclear RNAs (snRNAs), termination depends on specialized processing of the 3′ ends and often requires the Integrator complex, whose nuclease activity at specific cleavage sites is necessary for precursor transcript maturation (Baillat et al, 2005;Ezzeddine et al, 2011Ezzeddine et al, , 2012Uguen and Murphy, 2003) . Interestingly, transcription at motif-dependent piRNA loci shares evolutionary similarities to snRNA transcription (Beltran et al, 2019) .…”
Section: Introductionmentioning
confidence: 99%